Coffea arabica clones resistant to coffee leaf miner - Mendonça,Alex Paulo (2016)
Abstract Brazilian arabica coffee production is based on a set of highly productive cultivars sexually propagated. All of them are susceptible to coffee leaf miner, Leucoptera coffeella, and most of them are also susceptible to coffee leaf rust, Hemileia vastatrix. Aiming to reduce the selection process of cultivars with multiple resistances to both biotic constraints, the Coffea arabica clones 760, 1059, 1064 and 1215 were evaluated under field conditions. The mean yield of four C. arabica clones was not statistically different from the experimental controls; however, the yield of clone 1059 was 21% higher than the control cultivar Obatã IAC 1669-20. Leaf miner resistance level in all the evaluated clones remained the same as the mother plant's. However, the same did not occur for resistance to H. vastatrix, due to the emergence of new pathogen races. In summary, it is potentially feasible the adoption of clone 1059 as a new clonal cultivar resistant to coffee leaf miner.